Teori Ketuhanan Sigmund Freud Analisis Filsafat Ketuhanan Al Kindi - Harry Salam, Galang Risky (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This article describes the analysis of the weaknesses of Sigmund Freud's concept of divinity which is analyzed with the concept of Al Kindi's divine philosophy. The analysis uses a qualitative approach with exploratory and analytical methods. The result of this research is that Sigmund Freud's view of God cannot be justified, because it is only his subjective view that is far-fetched without conducting a deeper study of the essence and existence of God Himself. Freud only studied the psychological side of man, but he did not study the spiritual side of man himself. Al Kindi's view of God is more reliable because he explains the essence and existence of God based on empirical evidence that exists in nature, such as the novelty of nature, diversity in form, and the neatness of nature. He also explained that God is both the creator and the ruler of the universe. There is only one God and no one like Him. Besides Allah, it has many meanings. Therefore, in order to attain knowledge of God, it is necessary to conduct a deeper study in terms of man's intellect and spirituality so that he does not deny the existence of God.